Seeing is believing, experiencing is knowing: The influence of a co-designed prototype solar power plant on local acceptance - Enserink, Merel; Van Etteger, Rudi; Stremke, Sven (Solar energy, 2023)
•Action research to examine the influence of SPP prototype on local acceptance.•Prototype SPP helped to break status quo bias by understanding the potential impact.•Designers need to be aware of and address status quo bias when co-designing.•Results stress the importance of legitimacy of the process for local acceptance. The current approach to developing renewable energy projects often faces local opposition and has been said to increase injustice. One way of addressing procedural justice is to include local stakeholders in the design process. However, it can be difficult for lay audiences to understand the technical complexities of solar power plants. We built a full-scale prototype to support a participatory design process with local stakeholders and used engaged action research to examine the influence of this prototype on local acceptance in one real-life case in The Netherlands. The prototype helped to break the status quo bias. Furthermore, the study shows that well-designed participatory processes can aid understanding and help provide local stakeholders with possibilities to affect outcomes. Such processes can contribute to the legitimacy of the development of solar power plants and, in this case, increase local support for the development.